Implant-Retained Auricular Prosthesis: A Case Report - Ozturk, A Nilgun; Usumez, Aslihan; Tosun, Zekeriya (European Journal of Dentistry, 2010)
Extraoral implant retained prosthesis have been proven to be a predictable treatment option for maxillofacial rehabilitation. This case report describes the clinical and laboratory procedures for fabricating an auricular prosthesis.In this case report, an auricular prosthesis was fabricated for a patient who lost the left and right external ear in an electrical burn. Extraoral implants and bar-and-clip retention for the proper connection of the auricular prosthesis to implant were used. This prosthesis was acceptable to the patient because of excellent support, retentive abilities and the patients appearance. (Eur J Dent 2010;4:71-74)
Keywords: Auricular prosthesis; Implant retained prosthesis